Answer:
2m + 22
Step-by-step explanation:
Use the distributive property.
2(m + 11)
2 x m = 2m
2 x 11 = 22
Therefore, 2m + 22
Answer:
(2,-2)
Step-by-step explanation:
The first step is to substitute y in the first equation with the right side of the second equation because they both equal to y.
-3x+4 = 4x-10
-3x-4x+4-4 = 4x-4x-10-4
-7x = -14
-7x/-7 = -14/-7
x = 2
Plugin 2 for x for either equation to solve for y, I'll be using the second equation, but either one is fine.
y = 4(2)-10
y = 8-10
y = -2
Plugin x = 2 and y = -2 into (x,y), and you get (2,-2)
Answer: 19 ≥ 3z + 1 ≥ - 5
9514 1404 393
Answer:
4. height: 5√3 cm; area: 25√3 cm²
5. 30√2 ft ≈ 42.43 ft
Step-by-step explanation:
4. The height of an equilateral triangle is (√3)/2 times the side length, so is ...
height = (√3)/2 × (10 cm) = 5√3 cm
The area is given by the formula ...
A = 1/2bh
A = 1/2(10 cm)(5√3 cm) = 25√3 cm²
__
5. The diagonal of a square is √2 times the side length, so the distance from 3rd to 1st base is ...
(30 ft)√2 ≈ 42.43 ft
__
The length of the diagonal of a square is something you should be familiar with. If you're not, you can figure the distance using the Pythagorean theorem.
d = √(30² +30²) = √1800 ≈ 42.43 . . . feet